Escaping Chad’s Growth Labyrinth : Disentangling Constraints from Opportunities and Finding a Path to Sustainable Growth - World Bank Group (World Bank, Washington, DC, 2018)
This study seeks to understand the structure and workings of the labyrinth to propose a concrete escape. It attempts to answer the following questions. (1) Why is it that Chad could not translate the discovery of oil into structural development, economic diversification and sustainable growth? (2) What could possible pathways towards sustainable long run growth look like? (3) Which macro and micro policy actions could help build those pathways?